Implementation of the Kemuhammadiyahan Course in Shaping Religious Attitudes among the 2021 Cohort of Islamic Religious Education Students at Universitas Muhammadiyah Buton - Jumaydin, Jumaydin; Madi, Madi; Jusu, La (Universitas Muhammadiyah Enrekang, 2026)
This study examines the implementation of the Kemuhammadiyahan course in shaping the religious attitudes of the 2021 cohort of students in the Islamic Religious Education (PAI) program at Universitas Muhammadiyah Buton. Although the course is designed to inculcate Islamic and Muhammadiyah values, observed phenomena indicate that many students have not yet fully demonstrated religious attitudes in their campus life. Accordingly, this study aims to evaluate the extent to which the course implementation is effective in fostering students’ religious attitudes and to identify factors influencing the outcomes. The research employed a qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using Miles and Huberman’s interactive model, comprising data reduction, data display, and conclusion drawing/verification. The findings reveal that the predominance of lecture-based instruction, largely descriptive course content, and the lack of integrated co-curricular activities constitute the main factors limiting students’ application of religious values in their daily lives. In conclusion, strengthening the formation of religious attitudes requires renewed instructional strategies that are more interactive and contextually grounded, as well as the integration of relevant co-curricular activities aligned with Kemuhammadiyahan values.